2016
DOI: 10.1016/j.jvs.2015.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular aneurysm repair with contemporary volume-dependent sac embolization in patients at risk for type II endoleak

Abstract: This randomized study confirms that sac embolization during EVAR, using a sac volume-dependent dose of fibrin glue and coils, is a valid method to significantly reduce EII and its complications during early and midterm follow-up in patients considered at risk. Although further confirmatory studies are needed, the faster aneurysm sac volume shrinkage over time in patients who underwent embolization compared with standard EVAR may be a positive aspect influencing the lower EII rate also during long-term follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 21 publications
5
57
0
1
Order By: Relevance
“…11,12,17 Moreover, some reports have suggested that sac embolization during EVAR reduces ELII. 18,19 However, there is currently no strong evidence identifying which patients will benefit the most from preventive branch embolization to avoid ELII. 20 Target and routine embolization of side branches would be unnecessary and time consuming, considering the incidence of ELII and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,17 Moreover, some reports have suggested that sac embolization during EVAR reduces ELII. 18,19 However, there is currently no strong evidence identifying which patients will benefit the most from preventive branch embolization to avoid ELII. 20 Target and routine embolization of side branches would be unnecessary and time consuming, considering the incidence of ELII and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…When we compare the preventive sac embolization only (coils + glue) with selective sac branch embolization we can confirm that the selective approach is more efficient and has fewer artifacts and embolization materials. When we compare longer clinical outcomes, we can confirm there is no statistical evidence that sac preventive embolization has long-term efficiency as a technique to prevent EL2 [21,22]. It is recommended to embolize IMA and LA before SG deployment when the lumen diameter is more than 2-3 mm or if the number of patent LAs is more than 3.…”
Section: Discussionmentioning
confidence: 88%
“…This technique can have side effects regarding sac and neck dilatation, and expansion in the sac can lead to misplacement of the SG and further complications [20]. Aneurysm sac embolization [21,22] during the EVAR procedure using coils and glue can decrease the rise of endoleak, reduce sac volume, and improve its shrinkage. This method was described with a lower rate of reintervention due to EL2, but statistically, there was no clear outcome to confirm this technique as the best solution for prevention.…”
Section: Prevention Of El2mentioning
confidence: 99%
“…15,16 However, adverse events, such as colonic infarction and death that are related to the embolization of the aortic branches, were also reported. 17,18 Additional costs and these risks prevent pre-EVAR embolization from being a standard procedure in most vascular centers. Considering that most T2EL vessels stop flowing spontaneously, selective embolization of the T2EL vessels responsible for enlarging sacs as a prophylactic procedure is desirable, if possible.…”
Section: Discussionmentioning
confidence: 99%